2013
DOI: 10.1111/ejn.12242
|View full text |Cite
|
Sign up to set email alerts
|

Corticotropin‐releasing factor infusion into nucleus incertus suppresses medial prefrontal cortical activity and hippocampo‐medial prefrontal cortical long‐term potentiation

Abstract: The medial prefrontal cortex (mPFC) in the rat has been implicated in a variety of cognitive processes, including working memory and expression of fear memory. We investigated the inputs from a brain stem nucleus, the nucleus incertus (NI), to the prelimbic area of the mPFC. This nucleus strongly expresses corticotropin-releasing factor type 1 (CRF1 ) receptors and responds to stress. A retrograde tracer was used to verify connections from the NI to the mPFC. Retrogradely labelled cells in the NI expressed CRF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 52 publications
1
18
0
2
Order By: Relevance
“…Novel modulators have been found to play a role in reinstatement of alcohol drinking, because blockade of the relaxin-3 receptor RXFP3 by intra-BNST infusion of an antagonist attenuated cue-and stress-induced reinstatement of alcohol drinking in rats . Importantly, the neurons in the brain stemlocated nucleus incertus, which is the major source of relaxin-3 in the mammalian brain, are highly sensitive to stress and CRF (Banerjee et al, 2010;Farooq et al, 2013).…”
Section: Ethanol Administered In Vitro Enhanced Ipsps Andmentioning
confidence: 99%
“…Novel modulators have been found to play a role in reinstatement of alcohol drinking, because blockade of the relaxin-3 receptor RXFP3 by intra-BNST infusion of an antagonist attenuated cue-and stress-induced reinstatement of alcohol drinking in rats . Importantly, the neurons in the brain stemlocated nucleus incertus, which is the major source of relaxin-3 in the mammalian brain, are highly sensitive to stress and CRF (Banerjee et al, 2010;Farooq et al, 2013).…”
Section: Ethanol Administered In Vitro Enhanced Ipsps Andmentioning
confidence: 99%
“…The medial prefrontal cortex is of additional interest, as it forms a main source of afferent input into the NI (Goto et al, 2001). A recent study has also demonstrated that stimulation of CRF 1 positive NI neurons that project to the medial prefrontal cortex (either electrophysiologically or via administration of CRF) act to inhibit this region, while electrical or CRF-mediated stimulation of the whole NI impaired long term potentiation within the hippocampo-prelimbic medial prefrontal cortical pathway (Farooq et al, 2013). …”
Section: Relaxin-3/rxfp3 Signaling: a Novel Target For The Treatment mentioning
confidence: 99%
“…Certainly, based on what is known regarding the anatomical distribution of relaxin-3/RXFP3 networks and the prominent effects they can demonstrate on fundamental processes (such as coherent neural firing in the “septohippocampal system” and associated limbic circuits (Farooq et al, 2013; Ma et al, 2013) and effects on circadian activity related circuits (Smith et al, 2012; Blasiak et al, 2013), there is reason for optimism regarding its ability to be relevant therapeutically and to attract the attention of major Pharma.…”
Section: Future Studies Of the Relaxin-3/rxfp3 Systemmentioning
confidence: 99%
“…Moreover, selective pharmacogenetic activation of NI neurons causes enhanced arousal, locomotion, vigilance and active responding behaviours during fear conditioning 10 . CRF infusion into, or electrical stimulation of, the NI impairs long-term potentiation (LTP) of hippocampal-medial prefrontal cortical synapses 11 , whereas intra-NI infusion of the CRFR1 antagonist antalarmin reversed stress-induced suppression of LTP in this pathway 12 . Intra-NI infusion of the CRFR1 antagonist CP-376395, but not the CRFR2 antagonist astressin 2B, considerably reduced the reinstatement of alcohol seeking in rats that was induced by administration of the pharmacological stressor yohimbine 13 -an effect that is probably mediated by CRFR1 activation of relaxin-3-positive NI neurons 6,14 .…”
mentioning
confidence: 99%
“…Intra-NI infusion of the CRFR1 antagonist CP-376395, but not the CRFR2 antagonist astressin 2B, considerably reduced the reinstatement of alcohol seeking in rats that was induced by administration of the pharmacological stressor yohimbine 13 -an effect that is probably mediated by CRFR1 activation of relaxin-3-positive NI neurons 6,14 . The NI is therefore a stressresponsive nucleus and, through CRFR1, contributes to memory and learning, stressinduced reward seeking, impairments in neuronal plasticity, and arousal behaviours [9][10][11][12][13] .…”
mentioning
confidence: 99%